Biocultural heritage construction and community-based tourism in an important indigenous agricultural heritage system of the southern Andes - Kaulen-Luks, Santiago; Marchant, Carla; Olivares, Fernanda; Ibarra, Jose Tomas (My University, 2022)
Traditional agricultural systems reflect the close relationship between human communities and local ecosystems. The inheritance of knowledge, practices and beliefs, in which this relationship is materialised, or biocultural memory, is key for these systems' conservation and adaptation to social-environmental changes. Heritage construction processes may be used in a bid to conserve and increase awareness of this inheritance. Tourism is one alternative but is not immune to controversy. Through a qualitative methodology and participatory action research, this study examines biocultural heritage construction in an Important Agricultural Heritage System (IAHS) in Mapuche-Pewenche territory in the southern Andes. Based on the community-based tourism experience of two campesino cooperatives, our study points out how local actors understand and interpret their heritage as well as the opportunities and challenges of showcasing it through tourism. We found that the inheritance is understood as the way of life associated with Mapuche rural culture and, particularly, agricultural practices that support local food systems with a strong identity component. In these experiences of community-based tourism, we identify opportunities and challenges for reinforcing biocultural memory and inheritance in an IAHS. We discuss tourism development in IAHS sites, putting the communities that inhabit and maintain them in a central position.
Keywords: biocultural memory; community-based tourism; important agricultural heritage systems; local actors; participatory methodologies